Catalytic oxidation of benzene over ruthenium–cobalt bimetallic catalysts and study of its mechanism. Issue 1 (9th December 2016) - Liu, Xiaolong; Zeng, Junlin; Shi, Wenbo; Wang, Jian; Zhu, Tingyu; Chen, Yunfa
Abstract : A Ru–Co bimetallic catalyst was well demonstrated in benzene oxidation, and the reaction mechanism was studied. Abstract : In this work, ruthenium-based bimetallic catalysts of the formula Ru–5M/TiO2 (M = Mn, Co, Ce, Cu, Fe) were prepared and evaluated in benzene oxidation, and Ru–5Co/TiO2 exhibited the lowest complete oxidation temperature (220 °C), demonstrating Co3 O4 as the best dopant. The influence of the Ru and Co contents on the catalytic activity was also studied, and 1 wt% Ru and 5 wt% Co3 O4 were confirmed. Water vapor showed an inhibition effect on benzene oxidation at 210 °C, whereas the catalytic efficiency was barely influenced at a higher temperature (230 °C). STEM analyses revealed that Ru–Co bimetallic species showed similar distributions on the catalytic surface. Based on the correlation of the catalytic results with various characterization techniques, the synergistic effect between Ru and Co was well demonstrated, and a four-step transformation in the oxidation process was concluded. Besides, systematic in situ FTIR studies for benzene oxidation over Ru/TiO2, Co/TiO2, and Ru–5Co/TiO2 were conducted and compared, and many organic intermediates were observed in the in situ FTIR spectra. Accordingly, the reaction mechanism for benzene oxidation over the Ru–Co bimetallic catalyst was proposed.